Structural, Optical, Electrical and Discharge Characteristics of PVA-ZnS Nanocomposite Polymer Electrolyte−Zn2+ Ion Conduction for Solid State Battery Applications - Venugopal, R.; Sudhakar, K.; Narsimlu, N.; Srinivas, CH. (Asian Journal of Chemistry, 2023)
Polyvinyl alcohol (PVA) based Zn2+ ion conducting solid polymer electrolyte was prepared using a solution-cast method. Measurements were taken utilizing X-ray diffraction (XRD) and Fourier transform infrared analysis (FT-IR) to investigate the structure. The optical absorption spectra were investigated in the 200-800 nm range in order to acquire information about the optical properties of the material. This data comprised the direct energy gap, indirect energy gap and optical absorption edge of the material. The direct optical energy gap for pure PVA lies at 6.08 eV, while PVA doped with zinc sulphide ranges from 5.28 to 5.68 eV for the different compositions. It was evident that the energy gaps and band edge values transferred to lower energies on doping with ZnS up to a dopant concentration of 92 wt.% of PVA and 8 wt.% of ZnS. For this study, the ionic conductivity and transference number of PVA polymer electrolytes were measured in order to know more about the conductivity order and charge transport in these materials. The charge transport in PVA polymer electrolyte was measured to be largely due to ions (tion = 0.97), as indicated by the transference number. Increasing the ZnS concentration and the temperature were both found to raise the ionic conductivity. The discharge properties of solid-state battery cells made with this PVA polymer electrolyte were studied while operating under a constant load of 100 kW.